THE IMAGE OF A BIRD AS AN INDEPENDENT ELEMENT IN HISTORICAL AND ARCHITECTURAL OBJECTS - Sherzod Nurmanov (Western European Studies, 2024)
This article examines bird symbols in historical and architectural objects as independent elements. It analyzes how bird depictions in ancient monuments carry unique semantic and aesthetic significance, expressing religious, philosophical, and social ideas. The authors explore the symbolic meanings of birds in a historical and cultural context and their reflection in art. The article provides detailed insights into the role of bird symbols in defining national and regional identity and their significance in promoting spiritual values
Keywords: Bird symbols; historical and architectural objects; symbolic meaning